Gestión por procesos de la empresa lingle S.A.: subproceso operacional. - Luna Cun, Carla Lilibeth (My University, 2018)
The present investigation on Management by processes of the company Lingle S.A .: operational Subprocess had like objective identify bottlenecks in the shrimp culture of the company; For this purpose, a process map was prepared based on the company's situational analysis, a sub process was represented in a flow diagram, and the existence of bottlenecks was identified. The research was descriptive and the methodology was developed based on the literary work La Meta through four steps: Restrictions were identified, deicide how to exploit the bottlenecks to finally raise them. Bibliographic review of scientific articles, government institutions, documentation of international organizations EFQM and ISO was used, and an unstructured interview was applied to the manager of Lingle S.A. and the manager of Andamar S.A. to compare results. It was identified that in Lingle S.A. there are four strategic processes, four operational processes and four support processes; In the sub-process of feeding there were bottlenecks that according to the volley method delay the time in which the shrimp reached 16 gr. besides, it spends more balanced than the feeder feeding method. For the optimization of the sub-process the feeding methodology was changed and the processes were restructured according to the EFQM model and the documentation was adapted as a fundamental part of the ISO 9001: 2015.
La presente investigación sobre Gestión por procesos de la empresa Lingle S.A.: Subproceso operacional tuvo como objetivo identificar cuellos de botella en el cultivo de camarón de la empresa; para ello se elaboró un mapa de procesos en base al análisis situacional de la empresa, se representó un sub proceso en un diagrama de flujos, y se identificó la existencia de cuellos de botella. La investigación fue descriptiva y la metodología se elaboró en base a la obra literaria La Meta a través de cuatro pasos: Se identificaron las restricciones, se deicidio cómo explotar los cuellos de botella para finalmente elevarlos. Se utilizó la revisión bibliográfica de artículos científicos, instituciones del gobierno, documentación de organismos internacionales EFQM e ISO, y se aplicó una entrevista no estructurada al gerente de Lingle S.A. y al gerente de Andamar S.A. para contrastar resultados. Se identificó que en Lingle S.A. existen cuatro procesos estratégicos, cuatros procesos operativos y cuatro procesos de soporte; en el sub-proceso de alimentación existieron cuellos de botella que de acuerdo al método de voleo retrasan el tiempo en el que el camarón alcanza los 16 gr. además que gasta más balanceado que el método de alimentación por comederos. Para la optimización del sub-proceso se cambió la metodología de alimentación y se reestructuraron los procesos según el modelo EFQM y se adaptó la documentación como parte fundamental de las normas ISO 9001:2015.
Keywords: GESTIÓN POR PROCESOS; CUELLOS DE BOTELLA; MAPA DE PROCESOS; EFQM; ISO 9001:2015